2022
DOI: 10.1063/5.0073844
|View full text |Cite
|
Sign up to set email alerts
|

Exploring optoelectronic properties of C-doped GaAs for photocathode application from first-principles calculation

Abstract: In the preparation process of negative electron affinity GaAs photocathodes, the p-type doped property is beneficial to photoemission, and the doping element is usually Be or Zn. In fact, C-doped GaAs material has been widely used due to its high activation rate, extremely low diffusion coefficient, and good thermal stability, whereas the influence mechanism of the C dopant on the performance of the GaAs photocathode is still unclear. In order to investigate the substitutional effect on C-doped GaAs, electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This property makes molybdenum disulfide Te, and I) and discussed the effect of preparation conditions (Mo-rich and S-rich conditions) on its thermodynamic stability. The results showed that the newly formed Mo nanobonds and energy band relaxation altered the electronic distribution of Mo atoms around and near the dopant [28]. G et al studied the substitution effect of C-doped GaAs using first-principles density-functional theory calculations.…”
Section: Introductionmentioning
confidence: 99%
“…This property makes molybdenum disulfide Te, and I) and discussed the effect of preparation conditions (Mo-rich and S-rich conditions) on its thermodynamic stability. The results showed that the newly formed Mo nanobonds and energy band relaxation altered the electronic distribution of Mo atoms around and near the dopant [28]. G et al studied the substitution effect of C-doped GaAs using first-principles density-functional theory calculations.…”
Section: Introductionmentioning
confidence: 99%